2022
DOI: 10.1001/jamanetworkopen.2022.37574
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Industry Payments to Physicians in the First 6 Years After Graduate Medical Training

Abstract: ImportanceFinancial incentives and conflicts of interest may influence physician decision-making. It is important to understand financial interactions between the pharmaceutical and medical device industries and newly independent physicians who have recently completed their graduate medical education using a national transparency program.ObjectiveTo identify trends in industry payments to recent graduates of Accreditation Council for Graduate Medical Education–accredited residency or fellowship programs in ort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…Elsewhere in JAMA Network Open , a team from the Accreditation Council for Graduate Medical Education (ACGME) and Johns Hopkins University School of Medicine examine these voluntary reports, and despite the apparent limitations of the data set—which doubtless undercounts actual payments, perhaps dramatically—their findings are compelling and support several specific policy changes.…”
supporting
confidence: 93%
See 3 more Smart Citations
“…Elsewhere in JAMA Network Open , a team from the Accreditation Council for Graduate Medical Education (ACGME) and Johns Hopkins University School of Medicine examine these voluntary reports, and despite the apparent limitations of the data set—which doubtless undercounts actual payments, perhaps dramatically—their findings are compelling and support several specific policy changes.…”
supporting
confidence: 93%
“…One unexpected finding was a lesser association between program directors (PD) receiving gifts and their residents doing so. Prior research has suggested a strong role modeling effect—when a mentor accepts gifts, their mentees learn that doing so is acceptable—but in a multivariable model, Hogan et al found just a 1% increase in the relative risk that residents in a program would accept gifts for each gift taken by their PD. Still, the average PD who took gifts appears to have received about 10 of them in the year, raising the risk that their residents will also take gifts that year by about 10%.…”
mentioning
confidence: 47%
See 2 more Smart Citations
“…In the new study, Misop Han, MD, and colleagues examined trends in industry payments to physicians over the six years after residency and other forms of graduate medical training in the United States. (See Han et al, 2009. )…”
mentioning
confidence: 99%